Aplikasi Sistem Terdistribusi Pada Sistem Informasi Absensi Berbasis Mobile Di Kantor Bpdashl Wampu Sei Ular - Jadi Olo Pangihutan; Tommy; Risko Liza (Universitas Harapan Medan, 2021)
In the current era of the covid-19 pandemic, for employee attendance attendance is still using the attendance system with a finger print and in my opinion it is very dangerous in employee attendance at this time during the covid-19 pandemic, because the hands of employees who have been absent are left behind in the attendance machine and I think it can spread covid-19 to other employees who want to be absent, so that the use of a distributed system application on the mobile-based attendance information system at bpdashl wampu sei snake has a good impact on users, where users can avoid the spread of covid-19 with services digital attendance provided by the application that was built so that employees no longer have to queue at the attendance machine and avoid touching the attendance machine. To build a distributed system application on a mobile-based attendance information system at the office of bpdashl wampu sei snake using Adroid Studio. Therefore, the author raised the title of a distributed system application application on a mobile-based attendance information system at the BPDASHL Wampu Sei Snake office, so that the prevention of employee attendance is not contagious because there is no physical contact by reducing touch. With the design of a distributed system application on this mobile-based attendance information system, it is hoped that it can trigger other developers to innovate more in designing the next system